Enfoque de género: rol de la mujer rural en la agricultura ecuatoriana - Rodríguez Vásconez, Mario Javier (2021)
Throughout the years, there has been a struggle for the position of women to maintain opportunities of participation against the male gender, since women have not always been seen as worthy of being involved in activities that were exclusively performed by men according to society. This research proposes to know what is the role of women in rural Ecuador and if gender equity is maintained in this important agricultural activity. By means of a bibliographic investigation, coming from books, articles, newspapers that gather statistics that show the current reality. The general objective of this work is to analyze the role played by rural women in Ecuadorian agriculture, as well as to describe the measures adopted in Ecuador that promote gender equality in rural areas and to substantiate the social opportunities that rural Ecuadorian women currently have. Through the analysis of information, it was possible to confirm that rural women still suffer double discrimination, due to their gender and social condition. The participation of any gender in this activity such as agriculture is of vital importance in terms of development and food security, Ecuador represents a scenario of productivity that provides many opportunities for social progress for the entire community, concluding that rural women do not have the same opportunities for social development compared to the other gender, which has limited their possibility of personal progress. Although governmental institutions have implemented policies for inclusion and promotion of gender equity, the application of these strategies is not taken advantage of in the daily life of rural women